High sedentary behavior and compromised physical capabilities in adult smokers despite the suitable level of physical activity in daily life - Vinicius Tonon Lauria; Evandro Fornias Sperandio; Agatha Caveda Matheus; Rodrigo Pereira da Silva; Marcello Romiti; Antônio Ricardo de Toledo Gagliardi; Rodolfo Leite Arantes; Victor Zuniga Dourado (Universidade Federal de Santa Catarina, 2017)
Sedentary behavior may play an important role for health outcomes, regardless of the amount of physical activity in daily life (PADL).We aimed to evaluate and compare sedentary behavior as well as physical capabilities in physically active smokers and non-smokers. Twenty-eight adult smokers and 38 non-smokers free of lung disease were matched for age, sex, body mass index, body composition, cardiovascular risk and moderate-to-vigorous PADL. Participants underwent spirometry, cardiopulmonary exercise test (CPET), six-minute walk test (6MWT), isokinetic dynamometry, and body composition (bioelectrical impedance).Despite the similar amount of moderate-to-vigorous PADL(median, 4.5h/week for smokers and 4.0h/week for non-smokers), smokers spent more time lying (median, 8.2h/week: 95% confidence interval, 5.4 to 19.1 vs. 6.1h/week: 3.7 to 11.2) and in sedentary activities (median, 100h/week: 66 to 129 vs. 78h/week: 55 to 122) compared to non-smokers. Smokers also presented worse spirometry, peak V'O2 and maximum heart rate in the CPET, 6MWT, and isokinetic indices (p<0.05). We observed a strong correlation between the time spent lying and spirometry (r = - 0.730) in smokers. Smoking is related to higher sedentary behavior, despite the suitable PADL. An appropriate PADL did not reduce the deleterious effects of smoking on physical capabilities. Interrupting sedentary behavior may be an appropriate intervention target in smokers for reducing the risk of diseases.